From Metabolic Syndrome to Neurological Diseases: Role of Autophagy - Maiuolo, Jessica; Gliozzi, Micaela; Musolino, Vincenzo; Carresi, Cristina; Scarano, Federica; Nucera, Saverio; Scicchitano, Miriam; Bosco, Francesca; Ruga, Stefano; Zito, Maria Caterina; Macri, Roberta; Bulotta, Rosamaria; et al. (Frontiers in Cell and Developmental Biology, 2021)
Metabolic syndrome is not a single pathology, but a constellation of cardiovascular disease risk factors including: central and abdominal obesity, systemic hypertension, insulin resistance (or type 2 diabetes mellitus), and atherogenic dyslipidemia. The global incidence of Metabolic syndrome is estimated to be about one quarter of the world population; for this reason, it would be desirable to better understand the underlying mechanisms involved in order to develop treatments that can reduce or eliminate the damage caused. The effects of Metabolic syndrome are multiple and wide ranging; some of which have an impact on the central nervous system and cause neurological and neurodegenerative diseases. Autophagy is a catabolic intracellular process, essential for the recycling of cytoplasmic materials and for the degradation of damaged cellular organelle. Therefore, autophagy is primarily a cytoprotective mechanism; even if excessive cellular degradation can be detrimental. To date, it is known that systemic autophagic insufficiency is able to cause metabolic balance deterioration and facilitate the onset of metabolic syndrome. This review aims to highlight the current state of knowledge regarding the connection between metabolic syndrome and the onset of several neurological diseases related to it. Furthermore, since autophagy has been found to be of particular importance in metabolic disorders, the probable involvement of this degradative process is assumed to be responsible for the attenuation of neurological disorders resulting from metabolic syndrome.